Sap stain fungi / Mohamad Haafiz Mohamad Kassim - Mohamad Kassim, Mohamad Haafiz (2005)
Sap stain fungi that occur in timber and timber product is a problem among the companies that produce the product from timber. Sap stain fungi will effect the surface of the timbers or logs or strongly damage their appearance. In addition sap stain fungi will incur big loss to the companies that produce the timber product. Several methods were used by researchers to decrease or avoid this problem. Therefore a lot of money was used, also the chemical that they used can effect our environment. These problems still occur until now, even though damage by sap stain fungi in timber was studied centuries ago.